Topical prazosin attenuates sensitivity to tactile stimuli in patients with complex regional pain syndrome. (16th November 2015) - Drummond, Eleanor S.; Maker, Garth; Birklein, Frank; Finch, Philip M.; Drummond, Peter D.
Abstract: Background: The sympathetic nervous system may play an important role in certain forms of chronic pain. The main aim of this study was to determine whether functional blockade of α1 ‐adrenoceptors would alter sensitivity to cutaneous stimulation in patients with complex regional pain syndrome (CRPS). Methods and Results: In an initial study, high‐performance liquid chromatography‐mass spectrometry of intradermal interstitial fluid collected from the forearms of three healthy individuals established that the α1 ‐adrenoceptor antagonist prazosin penetrated the skin barrier when mixed in Lipoderm ® cream base. Next, we found that application of this cream to the forearm of 10 healthy participants attenuated axon reflex vasodilatation to the iontophoresis of phenylephrine, demonstrating functional blockade of α1 ‐adrenoceptors. Subsequently, effects of the cream on sensitivity to mechanical and thermal stimulation were investigated in 14 healthy participants and 19 patients with CRPS (eight with an apparent adrenergic component of pain). Both in patients and controls, topical application of the prazosin cream increased sensitivity to skin cooling but reduced sensations evoked by gentle brushing. In addition, hyperalgesia to sharp stimulation was lower at the prazosin‐ than vehicle‐treated site in the CRPS‐affected limb, and allodynia to brushing was lower at the prazosin‐treated than vehicle‐treated site in patients with an adrenergic component of pain. Conclusions: Prazosin cream inhibited adrenergic axon reflex vasodilatation in healthy volunteers, and also inhibited dynamic allodynia and punctate hyperalgesia in the CRPS‐affected limb of some patients. Further studies are required to assess the potential benefits of topically applied prazosin for CRPS.